The use of primary and secondary treated municipal wastewater for cucumber irrigation in hydroponic system - Pilatakis, G.; Manios, Thrassyvoulos; Tzortzakis, Nikos G. (My University, 2013)
Municipal wastewater may be used in agriculture but requires a careful monitoring of several hygiene parameters. The impact of direct application of treated wastewater in plant growth and development in hydroponically grown cucumber was studied. Cucumber seedlings used under 5 treatments of nutrient solution, which were basic nutrient solution (control), primary (PA) and secondary (SA) wastewater with or without nutrient solution enrichment (NS). The use of PA ± NS reduced plant height, leaf number and flowers produced as well as leaf size in cucumber plants but increased stem diameter. When SA ± NS used, no similar changes observed. The increased fruit number and fresh weight, when PA and SA used, resulted in increased yields as marked at the first week. The NS enrichment in PA reduced (up to 25%) plant yield while no differences observed in total fruit number among the treatments. No differences observed in plant biomass, root length and leaf chlorophyll levels among the treatments. The leaf photosynthetic rate and stomatal conductance increased in plant grown in PA ± NS and SA, but they did not differ in SA ± NS. The use of wastewater resulted in disease spread in roots and fruits (by cross-contamination). Further exploitation is necessary for microbial load reduction with wastewater application.
Keywords: Cucumis sativus L.; Fertigation; Nutrient film technique; Plant growth; Wastewater reuse